The Strong Consistency of the Estimator of Fixed-Design Regression Model under Negatively Dependent Sequences - Xuejun Wang; Meimei Ge; Shuhe Hu; Xize Wang (Abstract and Applied Analysis)
We study the strong consistency of estimator of fixed design regression model under negatively dependent sequences by using the classical Rosenthal-type inequality and the truncated method. As an application, the strong consistency for the nearest neighbor estimator is obtained.